Diabetes mellitus and risk of thyroid cancer: a meta-analysis. - Yohwan Yeo (Public Library of Science (PLoS), 2014)
Introduction Diabetes mellitus (DM) is an important risk factor for endocrine cancers; however, the association with thyroid cancer is not clear. We performed a systematic review and meta-analysis to clarify the association between thyroid cancer and DM. Methods We searched MEDLINE, PUBMED and EMBASE databases through July 2012, using search terms related to diabetes mellitus, cancer, and thyroid cancer. We conducted a meta-analysis of the risk of incidence of thyroid cancer from pre-existing diabetes. Of 2,123 titles initially identified, sixteen articles met our inclusion criteria. An additional article was identified from a bibliography. Totally, 14 cohort and 3 case-control studies were selected for the meta-analysis. The risks were estimated using random-effects model and sensitivity test for the studies which reported risk estimates and used different definition of DM. Results Compared with individuals without DM, the patients with DM were at 1.34-fold higher risk for thyroid cancer (95% CI 1.11-1.63). However, there was heterogeneity in the results (p<0.0001). Sensitivity tests and studies judged to be high quality did not show heterogeneity and DM was associated with higher risk for thyroid cancer in these sub-analyses (both of RRs = 1.18, 95% CIs 1.08-1.28). DM was associated with a 1.38-fold increased risk of thyroid cancer in women (95% CI 1.13-1.67) after sensitivity test. Risk of thyroid cancer in men did not remain significant (RR 1.11, 95% CI 0.80-1.53). Conclusions Compared with their non-diabetic counterparts, women with pre-existing DM have an increased risk of thyroid cancer.